Sildenafil increases serum testosterone levels by a direct action on the testes. (18th September 2013) - Spitzer, M.; Bhasin, S.; Travison, T. G.; Davda, M. N.; Stroh, H.; Basaria, S.
Summary: Phosphodiesterase‐5‐inhibitors, such as sildenafil, increase intracavernosal cyclic guanosine monophosphate levels, which results in corporal smooth muscle relaxation and penile erection. Here, we determined the effects of sildenafil administration on the hypothalamic‐pituitary‐gonadal axis in men with erectile dysfunction and low testosterone levels. The Testosterone and Erectile Dysfunction trial (ClinicalTrials.gov # NCT00512707) initially administered an optimized dose of sildenafil to 140 men, aged 40–70 years with erectile dysfunction, low serum total testosterone (<11.4 nmol/L; 330 ng/dL) and/or free testosterone (<173 pmol/L; 50 pg/mL) over 3–7 weeks. Sex steroids and gonadotropins were measured at baseline and after sildenafil optimization in a longitudinal study without a separate control group. Serum testosterone, dihydrotestosterone (DHT) and oestrogens were measured using liquid chromatography‐tandem mass spectrometry. Administration of an optimized dose of sildenafil was associated with mean increases of 3.6 nmol/L (103 ng/dL; p  <   0.001) and 110 pmol/L (31.7 pg/mL; p  <   0.001) in total and free testosterone levels respectively. This was accompanied by parallel increases in serum DHT (0.17 nmol/L; 4.9 ng/dL; p  <   0.001) and oestradiol (14 pmol/L; 3.7 pg/mL; p  <   0.001) and significant suppression of luteinizing hormone (change −1.3 units/L; p  =   0.003) levels, suggesting a direct effect at the testicular level. Androstenedione and oestrone increased by 1.3 nmol/L (38 ng/dL; p  =   0.011) and 10.7 pmol/L (2.9 pg/mL; p  =   0.012), respectively, supporting a possible effect of sildenafil on adrenal steroidogenesis. In conclusion, sildenafil administration was associated with increased testosterone levels likely ascribable to a direct effect on the testis.